Repeated ionizing radiation exposure induces TRIP13 expression, conferring radioresistance in lung cancer cells - Wenqing Liu; Qijing Lei; Ans M. M. van Pelt; Geert Hamer (Scientific Reports)
Abstract Radiation therapy is a common treatment modality for lung cancer, and resistance to radiation can significantly affect treatment outcomes. We recently described that lung cancer cells that express more germ cell cancer genes (GC genes, genes that are usually restricted to the germ line) can repair DNA double-strand breaks more rapidly, show higher rates of proliferation and are more resistant to ionizing radiation than cells that express fewer GC genes. The gene encoding TRIP13 appeared to play a large role in this malignant phenotype. However, the molecular regulatory mechanism of TRIP13 in radiation resistance remained largely unknown. Here, we show that TRIP13 is a key contributor to non-small cell lung cancer (NSCLC) treatment resistance, particularly in patients following radiation treatment, for whom levels of TRIP13 expression are correlated with a poor prognosis. Repeated irradiation of led to an increase of basal TRIP13 levels and radioresistance. This effect of radioresistance could be enhanced or abrogated by overexpressing or knocking out TRIP13. Elevated TRIP13 is also correlated with enhanced repair of radiation-induced DNA damage. We further showed the proteins NBS1 and RAD51 (homologous recombination. HR) and XRCC5 (non-homologous end-joining, NHEJ) to act downstream of TRIP13, although inhibition of TRIP13 mostly reduced the HR associated proteins in response to induced resistance to irradiation. This study elucidates a novel mechanism of treatment resistance in NSCLC cells, in which TRIP13 promotes HR mediated DNA repair and resistance to ionizing radiation.